Discrete distributions based on inter arrival times with application to football data. Issue 1 (2nd January 2018) - Nadarajah, Saralees; Chan, Stephen
ABSTRACT: Motivated by McShane, Adrian, Bradlow and Fader [ Journal of Business and Economic Statistics, 26, 2008, 369–378], we introduce thirteen discrete distributions. We give explicit expressions for their probability mass functions. We analyze two football data sets and show that some of the proposed distributions provide better fits than the distribution due to McShane, Adrian, Bradlow, and Fader.